Description Of ECG Recycle and Coronary Angiography in Coronary Heart Disease Patients in dr Iskak Hospital - Karmiati, Karmiati; Sutrisno, Sutrisno (STIKes Surya Mitra Husada, 2018)
Background: Coronary heart disease is a major health problem in almost every country in the world and contributes to about 30% of all deaths worldwide. Proper diagnosis in patients with coronary heart disease will determine the accuracy of the procedure and will affect the patients healing and prognosis. Purpose : This study aims to describe the picture of ECG and coronary angiography in patients with coronary heart disease. Methods : The design of this study was descriptive with the patient population of coronary heart disease in the cardiac catheterization room of RSUD dr. Iskak Tulungagung. The sample size was 35 respondents taken with acidental sampling. The variables in this study are ECG image and coronary angiography results. Methods of data collection using observation sheet. The results showed 13 respondents (37.14%) results of ECG image injuri. While the results of angiography showed 27 (77.14%) of respondents there was a significant stenosis. Result : The result of research also got difference of result between ECG image and Coronary angiography where the respondent that picture ECG and Coronary Angiography fit as many as 23 respondent whereas between ECG picture and Coronary Angiography not suitable as much 12 respondents. Conclusion : In accordance with the number of accuracy of ECG in diagnosing coronary heart disease patients who ranged between 55% while in angiography accuracy rate 99% then can be drawn conclusion diagnostic patients with coronary heart disease using EKG can be a mistake of diagnosis by 45% compared angiografi which only 1%